The Hippo Signaling Pathway: The Trader of Tumor Microenvironment - Yang, Duo; Zhang, Na; Li, Meihua; Hong, Tao; Meng, Wei; Ouyang, Taohui (Frontiers in Oncology, 2021)
The Hippo pathway regulates cancer biology in many aspects and the crosstalk with other pathways complicates its role. Accumulated evidence has shown that the bidirectional interactions between tumor cells and tumor microenvironment (TME) are the premises of tumor occurrence, development, and metastasis. The relationship among different components of the TME constitutes a three-dimensional network. We point out the core position of the Hippo pathway in this network and discuss how the regulatory inputs cause the chain reaction of the network. We also discuss the important role of Hippo-TME involvement in cancer treatment.